STRATEGI PENGEMBANGAN USAHA KOPRA PUTIH DI KECAMATAN TEMBILAHAN HULU KABUPATEN INDRAGIRI HILIR - Kurniawan; Yeni Afiza; Nina Sawitri (Program Studi Agribisnis, Fakultas Pertanian, 2021)
A good understanding of the internal and external environment of white copra business is expected to produce the right strategy in developing the business. This aims to increase profits and develop white copra business in the future. The aim of this study is to formulate a white copra business development strategy in Tembilahan Hulu District, Indragiri Hilir Regency. The method used are matrix IFAS, EFAS, IE and SWOT. The results of this study indicate that the white copra business in Tembilahan Hulu District was in cell V with a strategy of hold and maintain. Several strategies that can be used based on a SWOT analysis are increasing production, cooperating with consumers outside the region, increasing quality and expanding market share.